Estudios ecofisiológicos en la Amazonia colombiana :1. Araza (Eugenia stipitata, Mc Vaugh). - Hernández Gómez, María Soledad; Melgarejo Muñoz, Luz Marina; Barrera García, Jaime Alberto (SINCHI, 2018)
Fruticultura